TEKNIS BUDIDAYA DAN PRODUKTIVITAS TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) DI LAHAN GAMBUT BANTUAN PEMERINTAH KABUPATEN ROKAN HILIR DAN KABUPATEN SIAK - Ahmad Wardhani; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The oil palm plant (Elaeis guineensis Jacq) is one of the commodities star in the plantation subsector. The development of oil palm plantation area in Indonesia, especially in Riau has increased quite rapidly from year to year. This can be seen from the total area of oil palm plantations in Riau which is one of the largest palm oil producer in Indonesia. An increase in demand for processed oil palm products, encourage the district government made effort to improve the well-being of people through the program of economic based oil palm plantations. The objective of the research is to study the technical the cultivation and productivity of oil palm plants by the district government Rohil and Siak. The research has been conducted in Rantau Bais village, Tanah Putih district, Rokan Hilir and Kotoringin village, Mempura district, Siak for 3 months from June 2014 to August 2014. This research use sampling technique survey method, determining of location research purposive and random sampling, descriptive analysis presented in the form of list or tables observation. The results of the research showed cultivation technical in Siak more than reference on the recommendations made PPKS than Rokan Hilir, resulting in differences in productivity in both the district. The highest FFB production in Rokan Hilir is 890.2 kg/ha and the lowest FFB production is 679.7 kg/ha. The highest FFB production in Siak is 1.209.2 kg/ha and the lowest FFB production is 877.5 kg/ha. Keywords: Technical cultivation, oil palm productivity, Rokan Hilir and Siak